Admissibility of Estimated Regression Coefficients Under Generalized Balanced Loss - Hong-Bing Qiu; Ji Luo; Jiajia Zhang (Український математичний журнал, 2015)
There are some discussions concerning the admissibility of estimated regression coefficients under the balanced loss function in the general linear model. We study this issue for the generalized linear regression model. First, we propose a generalized weighted balance loss function for the generalized linear model. For the proposed loss function, we study sufficient and necessary conditions for the admissibility of the estimated regression coefficients in two interesting linear estimation classes. Ведуться дєякі дискусії щодо допустимості оцінєних коєфіцієнтів регресії для збалансованої функції втрат у загальній лінійній моделі. В роботі вивчається ця проблема для узагальненої лінійної моделі регресії. Так, запропоновано узагальнену зважену функцію втрати балансу для узагальненої лінійної моделі. Для вказаної функції втрат ми вивчаємо необхідні та достатні умови допустимості оцінених коефіцієнтів регресії для двох цікавих лінійних випадків оцінювання.